Correlation between serum α-Klotho levels and different stages of periodontitis - Can Ni; Dongyu Bao; Fuhua Yan; Bin Chen (BMC, 2023)
Abstract Background Periodontitis is an inflammatory disease characterized by inflammation and progressive destruction of periodontal tissues including alveolar bone. α-klotho protein is a multifunctional protein related to age-related diseases, inflammatory diseases, and bone metabolism-related diseases. However, large-sample epidemiological research evidence on the correlation between α-Klotho and the aggravation of periodontitis stages is still lacking. Methods Cross-sectional study data of participants aged between 40 and 79 years in the National Health and Nutrition Examination Survey 2013‒2014 were selected and analyzed. The stages of periodontitis of the participants were determined according to the 2018 World Workshop Classification of Periodontal and Peri-implant Diseases. The serum α-Klotho levels in people with periodontitis in different stages were evaluated. Then the correlation between serum α-Klotho levels and different stages of periodontitis was analyzed by multiple linear regression (stepwise regression method). Results A total of 2378 participants were included in the study. The serum α-Klotho levels in people with stage I/II, III and IV periodontitis were 896.16 ± 304.84, 871.08 ± 266.42 and 840.52 ± 286.24 pg/mL, respectively. The levels of α-Klotho in people with stage IV periodontitis were significantly lower than those in people with stage I/II and III periodontitis. Linear regression analysis results showed that compared to stage I/II periodontitis, serum α-Klotho levels were significantly negatively correlated with stage III (B ± SE = -37.28 ± 16.00, 95%  CI: -68.66 ~ -25.91, P = 0.020) and stage IV (B ± SE = -69.37 ± 16.11, 95%  CI: -100.97 ~ -37.77, P < 0.001) periodontitis. Conclusion The serum α-Klotho levels were negatively correlated with the severity of periodontitis. With the aggravation of periodontitis stages, the serum α-Klotho levels gradually decreased.